Study Of Early Thrombosis Factors Of Ateriovenous Fistula For Hemodialysis (Latakia University Journal -Medical Sciences Series, 2024)
Background:  Chronic renal failure is a public health problem worldwide with a significant morbidity and mortality rate that is increasing. Among the treatment options available for end-stage chronic renal failure, hemodialysis is the most widely used.To perform the dialysis, a temporary or permanent vascular access must be created, and the autogenous arteriovenous fistula is considered the most appropriate method, as it is a long-term access that allows effective and safe dialysis with a low infection rate and low medical care costs.Early thrombosis is defined as thrombosis that occurs within a month of the procedure and is diagnosed clinically (absence of thrill or pulsation by palpation or bruit  by auscultation) and by ultrasound.Objective: The research aims to study the risk factors that predict early thrombosis of an autogenous arteriovenous fistula prepared for  hemodialysis, thus reducing the incidence of failure and thrombosis.Methods: An Analytic Observational Study (Prospective) was conducted, in which 80 patients with ESRD who underwent new arteriovenous fistulas for  hemodialysis, during the period extending between the years 2022-2023, where the following variables were studied:  Age, gender, location of the fistula, diameter of the feeding artery, diameter of the vein, administration of anticoagulants, surgeon’s opinion, anastomosis technique.Patients were followed for one month after surgery and the outcome of the procedure was evaluated in terms of fistula maturation or thrombosis.Results: Early thrombosis occurred in 17 patients (21.2%).The thrombosis rate was higher in older ages (mean age 61.23±9.3), and was higher in females than males by 58.8%.No statistically significant differences were observed regarding the location of the arteriovenous fistula, except that 64.7% of cases of early thrombosis were in distal sites. The rate of early thrombosis cases was 76.5% with a venous diameter of less than 2 mm, and 52.9% with a feeding artery diameter of less than 2 mm.We did not find statistically significant differences between taking anticoagulants and the occurrence of early thrombosis of arteriovenous fistula.We did not find statistically significant differences between taking anticoagulants and the occurrence of early thrombosis of arteriovenous fistula.It was noted that 64.7% of cases of early thrombosis were with arteriotomy less than 6 mm, and there was no statistical significance with regard to the anastomosis technique using two sutures (P value = 0.5)